2018
DOI: 10.1525/jps.2018.47.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Reframing Public Health in Wartime: From the Biomedical Model to the “Wounds Inside”

Abstract: This article traces the research trajectory of the Institute of Community and Public Health (ICPH) at Birzeit University, whose work focuses on life and health outcomes for Palestinians living in chronic warlike conditions under Israeli settler-colonial rule. Over decades of field-based work, ICPH researchers came to the realization that medicalized responses to trauma contributed to concealing the social and political meaning that Palestinians attribute to their collective experience. By adopting an approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 29 publications
0
67
0
Order By: Relevance
“…Beginning work in the late 1980s, Giacaman found that traditional approaches to researching public health were unsuited to identifying the needs of the residents of the occupied Palestinian territories. Giacaman and her team adapted or replaced abstract and dehumanizing Western approaches, moving from reliance on “the biomedical model” of health to an attention to “the ‘wounds inside’” (Giacaman, 2018a). In a fascinating overview of the work of the ICPH, she highlights the growth in confidence in asserting an independent approach that begins with the knowledge of those at the margin itself:
For example, international researchers were asking, How can we get these violent Palestinian youth off the streets?, a framing that assumed Palestinian youth were violent by definition.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beginning work in the late 1980s, Giacaman found that traditional approaches to researching public health were unsuited to identifying the needs of the residents of the occupied Palestinian territories. Giacaman and her team adapted or replaced abstract and dehumanizing Western approaches, moving from reliance on “the biomedical model” of health to an attention to “the ‘wounds inside’” (Giacaman, 2018a). In a fascinating overview of the work of the ICPH, she highlights the growth in confidence in asserting an independent approach that begins with the knowledge of those at the margin itself:
For example, international researchers were asking, How can we get these violent Palestinian youth off the streets?, a framing that assumed Palestinian youth were violent by definition.
…”
Section: Resultsmentioning
confidence: 99%
“…Framing the question differently made it possible to expose the violations that Palestinian young people were experiencing, and the effects of those violations on their behavior, health, and well‐being, as well as their hopes for change and justice. (Giacaman, 2018a)“In the Palestinian context,” she continues, “where we had long been silenced and our narrative was disqualified (a practice that continues to prevail), knowledge production became part of the resistance to our settler‐colonial predicament… Our quest thus became one to reframe and measure the effects of political violence on the living beyond apparent physical health, uncovering the wounds inside, the invisible traumas of war that, cumulatively and over the life course, can lead to visible and diagnosable disease” (Giacaman, 2018a). Here we can see immediately the interface not only with mental health, but with psychoanalytic concerns with the large group impacts of traumatic social events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing political violence in the Palestinian context must be understood through a larger settler-colonial framework, characterized by Israel imposing systems of dispossession and control (Salamanca, 2012). This is done by the spatial constraint of Palestinian people and places via land takeovers, home invasions, and a series of Israelionly roads and checkpoints that take up upwards of 40% of Palestinian land in the West Bank (Hammami, 2015; United Nations Office for the Coordination of Humanitarian Affairs [UN-OCHA], 2007;Weizman, 2007); arbitrary and politically motivated arrests, detainments, and imprisonment (Giacaman & Johnson, 2013;McNeely et al, 2015); ongoing economic, educational, and social de-development (Barber et al, 2014;Roy, 2016); and humiliation and control (Giacaman, 2018;Sousa, Kemp, & El-Zuhairi, 2019).…”
Section: Geo-political Context Of Mothering In Palestinementioning
confidence: 99%
“…Trust in religion as a resort and a coping strategy can also be explained by the difficulties experienced by patients in accessing cancer care in the OPT. Treatments available are limited (in particular there are restrictions on radiation therapy due to security reasons; treatment plans can be delayed due to lack of medications); moreover, patients face many challenges in accessing the health system due to the military occupation and the restrictions to mobility (Giacaman, 2018;Hammoudeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%